2017
DOI: 10.5296/rbm.v4i2.11721
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Board Size on Firm Performance: Evidence from Ghana and Nigeria

Abstract: This paper examines the impact of corporate board size on firm performance for a sample of 137 listed firms in Ghana and Nigeria. Our findings suggest a statistically significant and positive relationship between board size and firm performance, implying that in Ghana and Nigeria allowing corporate board size to be dependent of firm size tends to improve firm performance. Our findings are consistent across different kinds of models that deal with different types of endogeneities and corporate performance proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 12 publications
3
24
1
1
Order By: Relevance
“…Those authors revealed that the increase of members on board potentiates the concerns of social policies. These results are aligned with stakeholders' theory as a large board size enhances the social dimension (Badu and Appiah, 2017;Kalsie and Shrivastav, 2016;Mallin and Michelon, 2011;Setia-Atmaja, 2018;Zhuang et al, 2018). Once again, these results allow us to corroborate H2.…”
Section: Regression Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Those authors revealed that the increase of members on board potentiates the concerns of social policies. These results are aligned with stakeholders' theory as a large board size enhances the social dimension (Badu and Appiah, 2017;Kalsie and Shrivastav, 2016;Mallin and Michelon, 2011;Setia-Atmaja, 2018;Zhuang et al, 2018). Once again, these results allow us to corroborate H2.…”
Section: Regression Results and Discussionsupporting
confidence: 85%
“…The board's main objective is to create wealth and value to stakeholders, including the process by which companies respond to the rights and requests of them (Cadbury, 2000;Demb and Neinbauer, 1992;Fadhilla and Hapsoro, 2017). Kalsie and Shrivastav (2016) and Badu and Appiah (2017) used Tobin's Q and ROA to address companies' economic dimension of sustainability. The authors argue that firm performance was positively influenced by board size, supporting agency theory.…”
Section: Corporate Governance Factorsmentioning
confidence: 99%
“…Temuan riset ini sejalan dengan penelitian Martín dan Herrero (2018), Yasser et al (2017), Badu (2017), dan Belkhir (2009) yang menemukan bahwa ukuran dewan direksi memiliki pengaruh positif dan signifikan terhadap kinerja keuangan. Penggabungan anggota baru ke dewan direksi memberikan pengetahuan kepada perusahaan sehingga meningkatkan profitabilitas ekonomi perusahaan (Martín dan Herrero, 2018).…”
Section: Pengaruh Dewan Direksi Terhadap Kinerja Keuanganunclassified
“…Some of these studies revealed an increase in the effectiveness of the company as the board of director's size grows. According to Agyemang Badu and Appiah (2017), agency perspective describes the size of the board depicting the level of control exercised by management, while some authors suggested the opposite. In effect, a decrease in the effectiveness of the company as the board of director's size grows.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%